2011
DOI: 10.1007/s12640-011-9253-z
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyl (PCBs)-Induced Oxidative Stress Plays a Critical Role on Cerebellar Dopaminergic Receptor Expression: Ameliorative Role of Quercetin

Abstract: Polychlorinated biphenyls (PCBs) exposure produces profound damage to the developing as well as adult central nervous system. Locomotor activities which are closely linked to dopaminergic neurotransmission are often impaired in PCBs toxicity. Targeting PCBs-induced oxidative stress using natural antioxidants is an attractive approach. Quercetin, a flavonoid is a safe and potent neuroprotective antioxidant. In this study, we sought to examine the protective role of quercetin against PCBs-induced neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Previous studies in our laboratory suggests that PCBs induces oxidative stress leading to neuronal apoptosis and alternative death pathways [31], disrupts dopaminergic system and calcium homeostatsis in cerebral cortex and cerebellum of rats [32,33]. Repeated exposure of adult rats to Aroclor 1254 induces neuronal injury and impaires the neurochemical manifestations of the NMDA receptor-mediated intracellular signaling in the hippocampus [28].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies in our laboratory suggests that PCBs induces oxidative stress leading to neuronal apoptosis and alternative death pathways [31], disrupts dopaminergic system and calcium homeostatsis in cerebral cortex and cerebellum of rats [32,33]. Repeated exposure of adult rats to Aroclor 1254 induces neuronal injury and impaires the neurochemical manifestations of the NMDA receptor-mediated intracellular signaling in the hippocampus [28].…”
Section: Discussionmentioning
confidence: 91%
“…Earlier studies in our laboratory reported that PCBs exposure impairs tight junctional proteins [31] and causes disruption of dopaminergic system in cerebral cortex and cerebellum of rat via the production of reactive oxygen species (ROS) [32,33]. PCBs-induced ROS production leads to oxidative/ nitrosative stress and cell death through over-activation of NMDARs both in culture and in animal models [34].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin's major circulating compounds in plasma were identified as quercetin 3-O-glucuronide, 3′-Omethylquercetin 3-O-glucuronide, and quercetin 3′-O-sulfate [32]. Once quercetin metabolites reach the blood flow, they are able to transverse the blood-brain barrier and are subsequently accumulated in the brain [33], where they exert their biological effects on the cerebellum [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibited LPS/IFN-ϒ induced p38 and STAT-1 phosphorylation [11]. However, Quercetin, improved behavioural function, suppressed oxidative stress, brain swelling, and cellular injury both in vitro and in vivo [12]. Although, Sesamol and Naringenin reversed both the rotenone/MPTP+-induced toxicity in PD rat model [4].…”
Section: Introductionmentioning
confidence: 98%